2019
DOI: 10.1021/acsbiomaterials.9b00947
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Paclitaxel-Loaded Aerosol Nanocomposite Microparticles and Their Efficacy Against Air-Grown Lung Cancer Tumor Spheroids

Abstract: Paclitaxel (as intravenous Taxol) is one of the most applied chemotherapeutics used for the treatment of lung cancer. This project involves the development of a dry powder nanocomposite microparticle (nCmP) aerosol containing PTX-loaded nanoparticles (NP) to be delivered via a dry powder inhaler to the lungs for the treatment of non-small cell lung cancer (NSCLC). Nanoparticles were formulated by a single emulsion and solvent evaporation method, producing smooth, neutral PTX NP of approximately 200 nm in size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…From this study, it was observed that the fine particle fraction (FPF) was 50.86 ± 2.80%, which is suitable for effective delivery to the lungs [9]. These particles would likely settle in the lower region of lung airways due to sedimentation (0.5-5 µm), whereas Brownian motion (0.5 µm) would cause stage 7 particles to settle in the alveoli [25]. However, the concentration of drug retained in the pre-separator is substantial with almost 22%, indicating scope for reducing this loss further by decreasing the size of the PLMs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…From this study, it was observed that the fine particle fraction (FPF) was 50.86 ± 2.80%, which is suitable for effective delivery to the lungs [9]. These particles would likely settle in the lower region of lung airways due to sedimentation (0.5-5 µm), whereas Brownian motion (0.5 µm) would cause stage 7 particles to settle in the alveoli [25]. However, the concentration of drug retained in the pre-separator is substantial with almost 22%, indicating scope for reducing this loss further by decreasing the size of the PLMs.…”
Section: Discussionmentioning
confidence: 94%
“…The drugs can be administered directly to the lung through oral inhalation, limiting systemic exposure, making it a promising noninvasive delivery route [7]. There are reports of DPIs of PTX prepared by spray-drying methods for lung cancer [22,25]. These systems have been found to be effective in the delivery of the drug through this system.…”
Section: Introductionmentioning
confidence: 99%
“…A Millipore water system (Direct Q @ UV) provided high purity of water that used for all experiments. A549 human lung adenocarcinoma epithelial cells were obtained and cultured as previously described …”
Section: Methodsmentioning
confidence: 99%
“…A549 human lung adenocarcinoma epithelial cells were obtained and cultured as previously described. 54 Preparation of [ML P ] and [ML P -DOX].…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Nanocarriers have been developed for PTX, as the hydrophobicity of PTX reduces its bioavailability. Recently, paclitaxel-loaded aerosol nanoparticles were synthesized and delivered to the lungs through a dry powder inhaler for treating NCSLC [79]. The size and morphology of the nanoparticles made them accessible to the distal region of the lungs.…”
Section: Paclitaxel-loaded Aerosol Nanoparticles For Drug Delivery In Lung Cancermentioning
confidence: 99%